2019
DOI: 10.1126/science.aax1184
|View full text |Cite
|
Sign up to set email alerts
|

Obesity remodels activity and transcriptional state of a lateral hypothalamic brake on feeding

Abstract: The current obesity epidemic is a major worldwide health concern. Despite the consensus that the brain regulates energy homeostasis, the neural adaptations governing obesity are unknown. Using a combination of high-throughput single-cell RNA sequencing and longitudinal in vivo two-photon calcium imaging, we surveyed functional alterations of the lateral hypothalamic area (LHA)—a highly conserved brain region that orchestrates feeding—in a mouse model of obesity. The transcriptional profile of LHA glutamatergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 43 publications
7
124
1
1
Order By: Relevance
“…Similar patterns of gene expression are observed in scRNA-Seq data obtained from Lhx6 neurons in the adult hypothalamus ( Fig. 18) (D. W. Mickelsen et al, 2019;Rossi et al, 2019). However, all these enriched markers (neuropeptides and neurotransmitters) are not specific to Lhx6 neurons but rather expressed broadly in hypothalamic GABAergic neurons ( Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similar patterns of gene expression are observed in scRNA-Seq data obtained from Lhx6 neurons in the adult hypothalamus ( Fig. 18) (D. W. Mickelsen et al, 2019;Rossi et al, 2019). However, all these enriched markers (neuropeptides and neurotransmitters) are not specific to Lhx6 neurons but rather expressed broadly in hypothalamic GABAergic neurons ( Fig.…”
Section: Resultssupporting
confidence: 79%
“…Differential peaks from ATAC-Seq between cortical and hypothalamic Lhx6-GFP + cells at P0. Mickelsen et al, 2019;Rossi et al, 2019).…”
Section: Statisticsmentioning
confidence: 99%
“…scRNAseq identifies transcriptionally distinct clusters among neuronal and non-neuronal cells. To characterize transcriptional identities of single cells in the mammalian habenula, we utilized droplet (Macosko et al, 2015;Rossi et al, 2019) based chromium technology developed by 10x Genomics (Zheng et al, 2017). We microdissected the habenula from brain live slices of adult male mice (P50-55), enzymatically digested the tissue to obtain well dissociated highly viable single cells (viability >80 %), captured single cell transcriptomes, and generated cDNA libraries for subsequent sequencing (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Dipatrizio and Piomelli (2015) reported that the ingestion of fat-rich foods initiates a cephalically-driven induction of endocannabinoid activity in the gut and maximizes food consumption [38]. Rossi et al (2019) reported that HFD weakened the activity of glutamatergic nerve cells in the lateral hypothalamus, which promoted overeating and obesity [39]. Furthermore, leptin resistance in obese individuals is a potential cause of eating disorders [40,41].…”
Section: Discussionmentioning
confidence: 99%